"Caregiver also need a caregiver": Reflections on the routine of mothers in a Pediatric Cardiological Nursing (Research, Society and Development, 2021)
Objective: To understand the routine of activities and the repercussions of the hospitalization of the companions of the pediatric ward in a cardiology hospital. Methods: Descriptive, cross-sectional research with qualitative analysis. The sample consisted of 7 mothers who were hospitalized with their children. The data were collected in 3 moments: sociodemographic questionnaire, instrument for routine hospital analysis and semi-structured interview. Discussion: Hospitalization involves an intense situation for mothers. Feelings such as anguish, fear and feelings of abandonment are common to arise. Despite praising the hospital's structure and professionals, they were dissatisfied with their activities and care routines. The accompanying mother became fragile and overwhelmed in the face of treatment, feeling vulnerable and, often, abandoned, corroborating the need for support from family members and health professionals. Conclusion: A child's hospitalization directly affects the lives of family members. In view of this, these professionals need to insert the family in their care plans, facilitating their interaction and providing actions that consider the singularities of the companion, such as listening, respect, bonding and welcoming.